Dysfunctional synapse in Alzheimer’s disease – a focus on NMDA receptors - Mota, Sandra I. (2014)
Alzheimer's disease (AD) is the most prevalent form of dementia in the elderly. Alterations capable of causing brain circuitry dysfunctions in AD may take several years to develop. Oligomeric amyloid-beta peptide (Aβ) plays a complex role in the molecular events that lead to progressive loss of function and eventually to neurodegeneration in this devastating disease. Moreover, N-methyl-d-aspartate (NMDA) receptors (NMDARs) activation has been recently implicated in AD-related synaptic dysfunction. Thus, in this review we focus on glutamatergic neurotransmission impairment and the changes in NMDAR regulation in AD, following the description on the role and location of NMDARs at pre- and post-synaptic sites under physiological conditions. In addition, considering that there is currently no effective ways to cure AD or stop its progression, we further discuss the relevance of NMDARs antagonists to prevent AD symptomatology. This review posits additional information on the role played by Aβ in AD and the importance of targeting the tripartite glutamatergic synapse in early asymptomatic and possible reversible stages of the disease through preventive and/or disease-modifying therapeutic strategies. This article is part of the Special Issue entitled ‘The Synaptic Basis of Neurodegenerative Disorders’.